La imagen devocional en los territorios de la monarquía hispánica después de Trento - Benavides, Jesús Porres (Cauriensia, 2023)
This paper analyzes the role of devotional images from their origins in Christianity, the Middle Ages and especially after the Counter-Reformation and the Council of Trent. Aspects such as iconoclasm in the Netherlands, influenced by Protestant areas, as well as iconoclastic areas in the Iberian Peninsula itself during the 16th century, are also touched on. Finally, the role played by the "trampe l'oeil to the divine" is reviewed as reflections of the generally sculptural "real images" and their expansion throughout the kingdoms of the Hispanic monarchy.